2016
DOI: 10.3390/molecules21111452
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Potential of Ethyl Acetate Fraction of Moringa oleifera in Downregulating the NF-κB Signaling Pathway in Lipopolysaccharide-Stimulated Macrophages

Abstract: Abstract:In the present investigation, we prepared four different solvent fractions (chloroform, hexane, butanol, and ethyl acetate) of Moringa oleifera extract to evaluate its anti-inflammatory potential and cellular mechanism of action in lipopolysaccharide (LPS)-induced RAW264.7 cells. Cell cytotoxicity assay suggested that the solvent fractions were not cytotoxic to macrophages at concentrations up to 200 µg/mL. The ethyl acetate fraction suppressed LPS-induced production of nitric oxide and proinflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 35 publications
4
49
0
Order By: Relevance
“…Our study showed that the control LPS-induced cells significantly increase in iNO, PGE 2 , IL1β and IL10 productions and TNF-α non-significantly in comparison to the normal cells. This was in agreement with other studies confirming the activation of signalling pathways, which leads to the release of pro-inflammatory cytokines, including IL1 β, TNF-α and mediators like NO and PGE 2 and anti-inflammatory cytokines like IL10 induced by LPS in RAW macrophage cells in the study [ 24 , 25 , 26 ]. The positive controls LNAME and quercetin in our study significantly reversed these effects.…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that the control LPS-induced cells significantly increase in iNO, PGE 2 , IL1β and IL10 productions and TNF-α non-significantly in comparison to the normal cells. This was in agreement with other studies confirming the activation of signalling pathways, which leads to the release of pro-inflammatory cytokines, including IL1 β, TNF-α and mediators like NO and PGE 2 and anti-inflammatory cytokines like IL10 induced by LPS in RAW macrophage cells in the study [ 24 , 25 , 26 ]. The positive controls LNAME and quercetin in our study significantly reversed these effects.…”
Section: Discussionsupporting
confidence: 93%
“…The results demonstrated that the MO extract strongly inhibited the LPS-induced expression of IL-6 and TNF-α during inflammation while increasing anti-inflammatory cytokine IL-10. Our present findings are consistent with a previous study fraction [17], which investigated the effects of different solvent fractions, including butanol, ethyl acetate, chloroform, and hexane of MO extract. The authors observed a decrease in IL-6, TNF-α, IL-1β, and prostaglandin E2 (PGE2) production in LPS-stimulated RAW264.7 macrophages after treatment with each solvent.…”
Section: Discussionsupporting
confidence: 93%
“…In Malaysia, fraction of MO leaves have been reported to be anti-inflammatory, by inhibiting Lipopolysaccharide (LPS)-induced production of nitric oxide and the pro-inflammatory cytokines in RAW264.7 cells [17]. Another study identified that isothiocyanates, bioactive from MO leaves extract, significantly inhibited the expression of iNOS, IL-1β, and the production of NO and TNF-β [18].…”
Section: Introductionmentioning
confidence: 99%
“…The fruit demonstrated the highest activity in reducing NO release induced by LPS in RAW264.7 cells (Lee et al, ). The fruit extract of MO blocked the atomic translocation of NF‐kB and increased inhibitor kB articulation (Arulselvan et al, ). MO roots showed evidence of restraint against IL‐2 activity (Sashidara et al, ).…”
Section: Resultsmentioning
confidence: 99%